The Impact of the Wheat Rht-B1b Semi-Dwarfing Allele on Photosynthesis and Seed Development Under Field Conditions - Jobson, Emma M.; Johnston, Rachel E.; Oiestad, Alanna J.; Martin, John M.; Giroux, Michael J. (Frontiers in Plant Science, 2019)
The Reduced Height (Rht) genes formed the basis for the green revolution in wheat by decreasing plant height and increasing productive tillers. There are two current widely used Rht mutant alleles, Rht-B1b and Rht-D1b. Both reduce plant height by 20% and increase seed yield by 5-10%. They are also associated with decreased seed size and protein content. Here we tested the degree to which Rht-B1b impacts flag leaf photosynthetic rates and carbon and nitrogen partitioning to the flag leaf and grain during grain fill under field conditions using near isogenic lines (NILs) that were either standard height (Rht-B1a) or semi-dwarf (Rht-B1b). The results demonstrate that at anthesis, Rht-B1b reduces flag leaf photosynthetic rate per unit area by 18% and chlorophyll A content by 23%. Rht-B1b significantly reduced grain protein beginning at 14 days post anthesis with the greatest difference seen at 21 days post anthesis (DPA) (12%). Rht-B1b also significantly decreased individual seed weight beginning at 21 DPA and by 15.2% at 28 DPA. Global expression analysis using RNA extracted from developing leaves and stems demonstrated that genes associated with carbon and nitrogen metabolism are not substantially altered by Rht-B1b. From this study, we conclude that Rht-B1b reduces flag leaf photosynthetic rate at flowering while changes in grain composition begin shortly after anthesis.